Description of two new species of Sycophilodes (Hymenoptera: Chalcidoidea: Epichrysomallidae) from China with a key to species of the genus - Yang, Xiao-Fang; Rasplus, Jean-Yves; Feng, Zhi-Rong; Miao, Bai-Ge; Peng, Yan-Qiong; Yang, Da-Rong; Chen, Huayan; Wang, Bo (Zootaxa, 2024)
Two new species of Epichrysomallidae (Hymenoptera: Chalcidoidea), Sycophilodes densfemur Yang, Peng and Rasplus sp. nov. and S. altissimae Yang, Peng and Rasplus sp. nov. are described and illustrated. These species are early gall makers developing in figs of Ficus altissima Blume, 1825 (Moraceae) in Xishuangbanna, China. Their biology is discussed and an identification key to the described species of Sycophilodes is provided.